The addition of rooibos tea extract (Aspalathus Linearis) as a natural antioxidant to South African Droëwors - Jones, Maxine (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc Food Sc)--Stellenbosch University, 2013.